Micropropagation of ginger (Zingiber officinale Roscoe) ‘Bentong’ and evaluation of its secondary metabolites and antioxidant activities compared with the conventionally propagated plant - Nisar Ahmad, Zahid; Jaafar, Hawa Z. E.; Mansor, Mohd Hakiman (MDPI, 2021)
‘Bentong’ ginger is the most popular variety of Zingiber officinale in Malaysia. It is vegetatively propagated and requires a high proportion of rhizomes as starting planting materials. Besides, ginger vegetative propagation using its rhizomes is accompanied by several types of soil-borne diseases. Plant tissue culture techniques have been applied in many plant species to produce their disease-free planting materials. As ‘Bentong’ ginger is less known for its micropropagation, this study was conducted to investigate the effects of Clorox (5.25% sodium hypochlorite (NaOCl)) on explant surface sterilization, effects of plant growth regulators, and basal media on shoots’ multiplication and rooting. The secondary metabolites and antioxidant activities of the micropropagated plants were evaluated in comparison with conventionally propagated plants. Rhizome sprouted buds were effectively sterilized in 70% Clorox for 30 min by obtaining 75% contamination-free explants. Murashige and Skoog (MS) supplemented with 10 µM of zeatin was the suitable medium for shoot multiplication, which resulted in the highest number of shoots per explant (4.28). MS medium supplemented with 7.5 µM 1-naphthaleneacetic acid (NAA) resulted in the highest number of roots per plantlet. The in vitro-rooted plantlets were successfully acclimatized with a 95% survival rate in the ex vitro conditions. The phytochemical analysis showed that total phenolic acid and total flavonoid content and antioxidant activities of the micropropagated plants were not significantly different from the conventionally propagated plants of ‘Bentong’ ginger. In conclusion, the present study’s outcome can be adopted for large-scale propagation of disease-free planting materials of ‘Bentong’ ginger.